Spark Plasma Sintering of Alumina- 15 wt.% Ceria Powder Prepared by Sol-Gel Method - S.A. Hassanzadeh-Tabrizi (Journal of Advanced Materials in Engineering)
In the present research, alumina-ceria particles were synthesized by a sol-gel method. The produced particles were characterized by X-ray diffraction and scanning electron microscopy. Then, alumina matrix composites containing 15 wt.% of ceria were densified under 80 MPa pressure at different temperatures by spark plasma sintering process. X-ray diffraction results showed that the powder produced before heat treatment has an amorphous structure, while alumina and ceria phases are formed after calcination at 800 °C. The produced particles have an average particle size of 250 nm. The effect of sintering temperature on the density of samples, grain size, and hardness of composites was investigated. The samples were densified at about 1400 °C, reaching a density of about 97% of the theoretical density. The microstructure analysis revealed that the composite grains have grown with increasing sintering temperature. The results declared that increasing the temperature and pressure in the sintering process enhances the density of the samples. The Vickers hardness of the composites increased with increasing sintering temperature, as the composite samples sintered at 1400 °C for 20 minutes at a pressure of 80 MPa had the highest Vickers hardness of about 15.3 GPa.